Tingkat Konsumsi dan Status Gizi Siswa Boarding School Sman 5 Gowa - Nuristha Febrianti; Sabaria Manti; Djunaidi M Dachlan; Nurhaedar Jafar; Marini Amalia Mansur (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Introduction: Adolescents need higher nutrition because of significant physical growth and body development, so adolescents need adequate food not only in terms of quantity but also in terms of quality. Adolescents tend to do the wrong eating behavior, that is the nutrients consumed do not suit their needs. Purpose: This study aims to determine the level of consumption and nutritional status of boarding school students at SMAN 5 Gowa. Material and Method: This type of research is observational with a descriptive research design. The sample of this study were 139 people using the Proportionate Stratified Random Sampling technique. Retrieval of consumption level data using 24-hour recall method. The determination of nutritional status is obtained from BMI / U parameters. Data processing and analysis in this research is univariate. Results: The results of the analysis revealed that the level of consumption for the respondents' macronutrient intake was still lacking namely less energy intake of 90.6%, less carbohydrates by 93.5%, less fat by 88.5% and less protein by 73.4%. The micronutrient intake of respondents was also lacking, namely vitamin A intake by 66.2%, vitamin B1 lacking by 94.2%, vitamin B12 by 88.5%, folate less by 99.3%, calcium less by 97.8%, iron less by 92.8% and zinc less by 92.8%. Whereas the nutritional status of respondents was classified as normal at 64.7%, very thin at 2.2% and obesity at 4.3%. Conclusion: The level of consumption of respondents for macro and micronutrient intake is still less than the recommended RDA needs and the respondent's nutritional status is normal.